Determinants of Foreign Direct Investment in Malawi - Chimbalu, Mkondana (Graduate School of Business (GSB), 2019)
This study examines empirically the determinants of Foreign Direct Investment in Malawi, by employing annual data that covered the period 1970-2016. The study used a dynamic model, the Autoregressive Distributed Lag bounds-testing approach to co-integration and error correction model, to explore these determinants. The study found that a long run relationship between Foreign Direct Investment and the selected determinants: market size, infrastructure, human capital, broad money, real exchange rate, population growth, government consumption, and inflation. The study further found that the determinants that were significantly associated with attracting Foreign Direct Investment in Malawi included infrastructure, broad money and government consumption. Specifically, the study results found that government consumption is negatively and significantly associated with Foreign Direct Investment both in the short and long run; infrastructure is positively and significantly associated with Foreign Direct Investment in the long run; broad money is positively and significantly associated with Foreign Direct Investment in the long run; and no significant relationship was found between market size, human capital, real exchange rate, population growth, and inflation both in the short and long run. These results have important policy implications for Malawi. These include the need for Malawian authorities to focus on strategies that create incentives to increase the level of physical infrastructure in the country; implementing monetary policies, fiscal incentives and subsidies that promote financial development; as well as promoting FDI-friendly government policies that minimise the impact of distortionary fiscal policies such as distortionary taxation and deregulation.